Assessment of Traditional Methods of Controlling Striga on Cultivated Crops in Sudanian Agricultural Zone of Chad - Naoura, Gapili; Amos, Doyam Nodjasse; Reoungal, Djinodji; Alfred, Djenaissem (International Journal of Applied Sciences and Biotechnology, 2021)
The phytoparasite, Striga spp., is a major biotic constraint to cereals production in sub-Saharan Africa. This study was carried out at station of Bébédjia of Chadian Institute of Agronomic Research for the Development in Sudanian agricultural zone of Chad, on traditional methods of controlling Striga spp. This study helped to find out several methods of controlling Striga among which the most important is the agronomic method including organic and or mineral fertilization, associated crops, crop rotation and the use of false hosts and trap crops. Some farmers cultivated resistant varieties and early maturing varieties to control pest attack and some others used shea flour and herbicide treatment to reduce the effect of Striga on the farm. Most of these methods were applied by farmers from generation to generation, without a thorough study to understand their mechanism. Thus, the listed methods will be analysed by research in station to find out scientific explanations for each applied method. Then experiments will be carried out to evaluate the effectiveness of some methods previously identified by extension rural services in farmers’ area after improvement.